Curcumin and resveratrol rescue cortical–hippocampal system from chronic fluoride-induced neurodegeneration and enhance memory retrieval. (2nd November 2018) - Sharma, Chhavi; Suhalka, Pooja; Bhatnagar, Maheep
ABSTRACT: Objective : The aim of this study was: (1) to evaluate the neuroprotective effect of resveratrol and curcumin on nicotinamide adenine dinucleotide phosphate diaphorase activity in neuronal cell in subregions of mice brain, (2) to evaluate the effects on antioxidant status and (3) to evaluate the protective effects of phytochemicals on learning and memory following fluoride exposure. Method: Young mice (one month old, body weight (BW) 30 ± 5 mg) were provided with 120 ppm sodium fluoride dissolved in drinking water. They were given curcumin (30 mg/kg BW) or resveratrol (30 mg/kg BW) orally once in a day up to 30 days. Effects of resveratrol and curcumin on spatial learning and memory were studied using Morris water maze and classic maze test. Effects on brain antioxidants' (lactose dehydrogenase (LDH), malondialdehyde and reactive oxygen species) status were also studied in vitro . Histochemistry was done to assess the effect of treatments on nitric oxide neurotransmitter. Result: Our study showed that in fluoride-treated animals, the number of nicotinamide adenine dinucleotide phosphate diaphorase positive neurons, intracellular Ca 2+, reactive oxygen species level, LDH and malondialdehyde concentration increased significantly. Interestingly, after treatment with curcumin or resveratrol, a significant decrease in the number of nicotinamide adenine dinucleotide phosphate diaphorase positive neurons and antioxidant status was observed. This decrease was more considerable in resveratrol-treated group. Conclusion: Our study indicates that both antioxidants, curcumin and resveratrol, are useful in reducing neurodegeneration in selective areas of cornus ammonis 1 (CA1), CA3, dentate gyrus (DG) and the cortex of mice brain and in recuperating the loss of memory and learning caused due to fluoride exposure.